IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS WEBLOG DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 51 SURABAYA - Maisaroh, Siti; Huda, M Masrur; Kartika, Nuril; Nadhiroh, Aniswatun (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
This thesis discusses the effectiveness of the implementation of weblog-based Islamic Religious Education learning media as a medium and learning resource in increasing students' interest in learning at SMP Negeri 51 Surabaya. This study aims to determine the effectiveness of the implementation of weblog-based Islamic Religious Education learning media as a learning resource in increasing interest in learning students at SMP Negeri 51 Surabaya. This study uses a qualitative research design. field research (Field Research), researchers go directly to the field or are carried out in schools through observation, interviews, and documentation studies, in order to obtain clear and representative data. The results of this study indicate, (1) Teachers use weblog-based Islamic Religious Education learning media at SMP Negeri 51 Surabaya. The use of weblogs in the learning process of Islamic Religious Education as a medium and learning resource has an impact on students' learning interest. (2) Students at SMP Negeri 51 Surabaya have an interest in studying Islamic Religious Education. Islamic Religious Education teachers using weblog-based learning media in the learning process have an impact on focusing attention, feeling happy, and enthusiastic as well as students' interest in learning the material and answering quizzes given on weblogs (3) The use of weblog-based Islamic Religious Education learning media has an impact in increasing students' interest in learning at SMP Negeri 51 Surabaya.